2005
DOI: 10.1038/sj.onc.1208896
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cell turnover in lymphocytic monkeys infected by human T-lymphotropic virus type 1

Abstract: Understanding cell dynamics in animal models have implications for therapeutic strategies elaborated against leukemia in human. Quantification of the cell turnover in closely related primate systems is particularly important for rare and aggressive forms of human cancers, such as adult T-cell leukemia. For this purpose, we have measured the death and proliferation rates of the CD4 þ T lymphocyte population in squirrel monkeys (Saimiri sciureus) infected by human T-lymphotropic virus type 1 (HTLV-1). The kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Of note, studies of the first STLV-3-infected animals were reported almost a decade ago (14), but those animals as well as the STLV-3-infected monkeys described more recently (24,25,27,48,51) were never studied longitudinally. For this reason, it is not possible to determine whether, as is the case for some STLV-1-infected animals, animals can suffer from adult T-cell leukemia/lymphoma-like or other diseases (9). We have now sequenced the HTLV-3 provirus, which is very similar to a central African STLV-3 strain (STLV-3 CTO604 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, studies of the first STLV-3-infected animals were reported almost a decade ago (14), but those animals as well as the STLV-3-infected monkeys described more recently (24,25,27,48,51) were never studied longitudinally. For this reason, it is not possible to determine whether, as is the case for some STLV-1-infected animals, animals can suffer from adult T-cell leukemia/lymphoma-like or other diseases (9). We have now sequenced the HTLV-3 provirus, which is very similar to a central African STLV-3 strain (STLV-3 CTO604 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits proved to be an effective model for HTLV-1 infection (1,65). In addition, monkeys and rats have been used to analyze the in vivo proliferation of HTLV-1-infected cells (7,55). Furthermore, immunodeficient mouse strains were also able to engraft some HTLV-1-immortalized cell lines (13,24).…”
mentioning
confidence: 99%
“…However, the life expectancy of a lymphocyte is not an intrinsic property of the cell but is determined by factors such as the environment, viral infections, and the presence or absence of another, competing, cell population. We previously studied lymphocyte homeostasis, more particularly, lymphocyte proliferation and death, in different animal models of chronic leukemia, including sheep infected by the bovine leukemia virus (BLV) (7)(8)(9). In this model, proliferation was estimated by intravenous injection of bromodeoxyuridine (BrdU), a thymidine analog which is incorporated into the newly synthesized DNA via the pyrimidine salvage pathway.…”
mentioning
confidence: 99%